(untitled) (Eurasian Journal of Ecology, 2022)
The article monitors climatic changes in the distribution zones of the rare, medicinal species Adonis tianschanica Lipsch using the GIS method. Distribution areas of the species: population 1 – Kegen Pass, population 2 – Dzungarian Alatau (Tekeli), population 3 – Terskei Alatau. The article discusses 19 different databases describing the climate, and provides a link to all databases. To compare the two databases, CHELSEA 2.1 (CA) and WorldClim v1, v2 (WC) were selected. The description of the database took into account spatial resolution (data tolerance and spatial scale), periods (covered periods and frequency of data), the main important climatic information (temperature, precipitation). When the data set was available by month, long-term averages were calculated for comparison (1980-1999, 2000-2018). To reduce the number of maps, only annual values were compared. According to the average temperature and the amount of precipitation for these periods (1980-1999, 2000-2018), 16 maps were compiled for 2 databases in which the data were compared and evaluated. According to the air temperature – the average and maximum average, information is given about the percentage of differences, maximum, minimum temperatures. According to the amount of precipitation 1980-1999, 2000-2018, information on precipitation on average for the period is provided. We have to say that such a comparison is not a database check. According to expert knowledge, we can compare and represent only variables with the appropriate distribution and avoid databases that differ significantly from others (for example, WorldClim v2 for temperature). Key words: Adonis tianschanica Lipsch (Adolf), endem, population, climate, Dzungarian Alatau, Terskey Alatau, temperature, precipitation.